PENDAMPINGAN PENCATATAN USAHA UNTUK UNIT USAHA KIT PANDERMAN - Christiawan, Giovanni; Helios, Christover; Jedija, Jehu; Jonathan, Peter; Pratama, Bagas Brian; Anugrah, Audito Aji; Oktariani, Fitri; Cahyadi, Rino Tam (Jurnal Pengabdian Bukit Pengharapan, 2024)
The business recording assistance for Kit Panderman was written and conducted to fulfill the course requirements for Accounting for Entrepreneurship and to help the business unit calculate its total expenses and revenues. The purpose of this activity is to provide assistance in accounting recording, so they can manage their finances better and make accurate business decisions. The implementation method includes direct teaching and counseling at the business location and through online media. The results show that the implementation of financial recording templates helps business owners in recording daily expenses, revenues, and systematically calculating profit or loss. Initial challenges faced, such as understanding cost recording, can be overcome through continuous assistance. Overall, the business owners felt helped by the template, which allowed them to have a clearer view of their financial condition and improve their operational efficiency. In conclusion, this assistance activity successfully improved Kit Panderman's financial management capabilities and reduced errors in their financial recording.